2006
DOI: 10.1016/j.jtcvs.2005.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial injury and acquired aspirin resistance as promoters of regional thrombin formation and early vein graft failure after coronary artery bypass grafting

Abstract: Aspirin resistance and relatively compromised venous endothelial cell integrity together marked patients whose vein grafts failed within days after off-pump coronary artery bypass grafting. These observations form a basis for identifying patients at risk and developing approaches to prevent vein injury or to selectively intervene in high-risk circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 34 publications
3
88
1
2
Order By: Relevance
“…In addition, these investigations demonstrate a clear correlation between the extent of coronary artery disease and ASA hyporesponsiveness (Table 4, Figure 4). This correlation between ASA hyporesponsiveness and CAD severity is consistent with previous reports demonstrating persistent formation of TX in ASA-treated patients with CAD requiring surgical revascularization 39 and in patients with known severe CAD 40 . Mechanistically, a higher inflammatory milieu in patients with extensive CAD might promote platelet activation and thus contribute to ASA hyporesponsiveness.…”
Section: No Of Patientssupporting
confidence: 92%
“…In addition, these investigations demonstrate a clear correlation between the extent of coronary artery disease and ASA hyporesponsiveness (Table 4, Figure 4). This correlation between ASA hyporesponsiveness and CAD severity is consistent with previous reports demonstrating persistent formation of TX in ASA-treated patients with CAD requiring surgical revascularization 39 and in patients with known severe CAD 40 . Mechanistically, a higher inflammatory milieu in patients with extensive CAD might promote platelet activation and thus contribute to ASA hyporesponsiveness.…”
Section: No Of Patientssupporting
confidence: 92%
“…208,216 By comparison, the current review found 57 distinct monotherapy studies overall 46 were also included in the seven previous reviews [207][208][209]211,[215][216][217] which provided any information on exclusion criteria (see Table 75). Conversely, of the studies included by at least one other review, the current review excluded 16 at the full-text stage 38, [235][236][237][238][239][240][241][242][243][244][245][246][247][248][249] and seven at the title and abstract stage, 250-256 as they did not meet the inclusion criteria. Three studies were included in other reviews which were not identified by the search strategy; one was subsequently excluded as it was a cross-sectional study, 256 while the correct citation was not identifiable for the other two studies.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…During intraoperative handling and temporary storage of the vessel segments in the course of bypass operations, the antigen expression level in the intima increases dramatically (52). Our laboratory has shown recently that surgical manipulation of venous bypass vessels often results in extensive endothelial lesions (73).…”
mentioning
confidence: 99%